2017
DOI: 10.3389/fpsyg.2017.01807
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Gambling Reinforcers, Over Consumption and Fallacies: The Psychometric Properties and Predictive Validity of the Jonsson-Abbott Scale

Abstract: Traditionally, gambling and problem gambling research relies on cross-sectional and retrospective designs. This has compromised identification of temporal relationships and causal inference. To overcome these problems a new questionnaire, the Jonsson-Abbott Scale (JAS), was developed and used in a large, prospective, general population study, The Swedish Longitudinal Gambling Study (Swelogs). The JAS has 11 items and seeks to identify early indicators, examine relationships between indicators and assess their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 34 publications
0
13
1
Order By: Relevance
“…The Swedish Longitudinal Gambling Study showed that heavy gambling involvement predicts gambling problems a year later (Jonsson, Abbott, Sjöberg, & Carlbring, 2017). It is also known that there is a high density of problem gamblers among those with high expenditure (Pallesen, Molde, Mentzoni, Hanss, & Morken, 2016; Public Health Agency of Sweden, 2016).…”
mentioning
confidence: 99%
“…The Swedish Longitudinal Gambling Study showed that heavy gambling involvement predicts gambling problems a year later (Jonsson, Abbott, Sjöberg, & Carlbring, 2017). It is also known that there is a high density of problem gamblers among those with high expenditure (Pallesen, Molde, Mentzoni, Hanss, & Morken, 2016; Public Health Agency of Sweden, 2016).…”
mentioning
confidence: 99%
“…The results of the CFA are presented in Table 1. When examining the values from the factor analysis in relation to the cutoffs, the three-factor structure is valid, has an acceptable fit for the sample, and is better than in Jonsson et al (2017a).…”
Section: Results From the Analysis That Investigate The Validitymentioning
confidence: 99%
“…The results from the person item map indicate a hierarchy regarding the subscales. From a theoretical perspective and in line with Jonsson et al (2017a), it appears that behavior that reinforces gambling is the first indicator of possible gambling problems, as it is most common in a low-risk population. The items most likely to be endorsed belonged to the factor Reinforcers, followed by two items in the factor Gambling fallacies.…”
Section: Practical Implications For the Jasmentioning
confidence: 94%
See 1 more Smart Citation
“…Neither scale evaluates predictors of gambling, rather the cognitive profiles of gamblers. The Jonsson-Abbott Scale (JAS) (Jonsson et al, 2017) seeks to identify early indicators, examine relationships between indicators and assesses their capacity to predict future problem progression. JAS has 11 items classified into three factors:…”
Section: Introductionmentioning
confidence: 99%